Exploring Financial Behaviour in MSME’s Sector: a Sytematic Review of Literacy, Attitude, and Gender Perspective - Murdiono, Achmad; Kurniawan, Fajar Azmi; Pratikto, Heri; Hermawan, Agus (CV. Proaksara Global Transeduka, 2025)
Financial behavior is a critical aspect of economic life, particularly for actors in the micro, small, and medium enterprises (MSMEs) sector. This study aims to systematically review academic literature on the influence of financial literacy, financial attitudes, and gender role on financial behavior, utilizing a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. This study was arranged to review in a systematic literature review approach, focusing on the influence of academic literature related to literacy finance, attitude finance, and gender roles in behavior finance, using a Systematic Literature Review (SLR) approach based on the PRISMA protocol. Sixty articles were selected from five academic databases (Scopus, ScienceDirect, Google Scholar, Emerald, and ProQuest), published between 2015 and 2025, and analyzed through thematic coding techniques. The results are relevant that financial literacy affects financial behavior directly and indirectly, mediated by attitude and intentions. Financial attitude is a key moderator in fostering responsible financial behavior. At the same time, gender is a moderate variable that influences the strength of the relationships among the variables. Moreover, behavioral characteristics differ among MSME actors, indicating the need for demographically contextualized interventions. This review emphasizes integrating financial literacy, attitude, and gender in shaping financial behavior. It supports the necessity for targeted financial education policies, including gender- and community-based approaches. The findings further affirm the relevance of theories such as the theory of planned behavior and mental accounting in understanding financial behavior in the digital era.